2007
DOI: 10.1123/japa.15.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibration Exercise on Muscle Performance and Mobility in an Older Population

Abstract: This study was designed to investigate the effects of vibration on muscle performance and mobility in a healthy, untrained, older population. Forty-three participants (23 men, 20 women, 66-85 y old) performed tests of sit-to-stand (STS), 5-and 10-m fast walk, timed up-and-go test, stair mobility, and strength. Participants were randomly assigned to a vibration group, an exercise-withoutvibration group, or a control group. Training consisted of 3 sessions/wk for 2 mo. After training, the vibration and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 38 publications
(46 reference statements)
1
90
1
12
Order By: Relevance
“…The nine studies that examined strength all found statistically significant improvements in muscular strength [1,5,28,33,35,36,41,49,51], and three studies suggested WBV is as effective as conventional resistance training [5,41,49]. Of the seven studies that examined balance, each one found statistically significant improvements in the components measured.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nine studies that examined strength all found statistically significant improvements in muscular strength [1,5,28,33,35,36,41,49,51], and three studies suggested WBV is as effective as conventional resistance training [5,41,49]. Of the seven studies that examined balance, each one found statistically significant improvements in the components measured.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…A pilot study examining polio patients was the only study that did not show increased strength benefits with WBV training [7]. For the remaining 13 articles specific to lower body strength, two main themes exist; WBV improves muscular strength in seniors (e.g., [2,28,49]), and WBV is as effective as conventional resistance training (e.g., [35,41]). …”
Section: Lower Extremity Power and Strengthmentioning
confidence: 99%
“…Therefore, consumption of creatine supplement increased isometric strength of the leg in elderly women for 10 days. Improvements in strength have been reported after WBW training (2,10,16,17,(30)(31)(32) in several previous studies with different durations. However, some other studies have not reported significant improvements in strength after WBW training (8,9).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, improvement in lower body function following training is subject to increased strength, and there is a strong relationship between strength and the ability to perform daily activities such as walking, getting up, and sitting on a chair, and climbing stairs. Moreover, several studies have found that increase in strength and improvement in performance occurred simultaneously (23,24,30). Accordingly, the increase in leg strength may be a possible mechanism for improvement in the 30-meter walking performance in our study.…”
mentioning
confidence: 75%
“…Estudo realizado por Stolzenberg et al 26 aponta que o treino de vibração associado ao treino de força promove melhora no controle postural de idosas com baixa densidades óssea. Entretanto, Rees et al 27 não encontrou diferenças significativas na força muscular dos extensores de joelho dos indivíduos idosos que realizaram 2 meses de treinamento com vibração em relação ao grupo de treinamento sem vibração.…”
Section: Discussionunclassified